Identifying Female Officer Potential: An Exploration in Predictors' Payoff - Tziner, Aharon; Dolan, Shimon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
This study examines the effectiveness of multi-predictor selection System as compared with any other alternative selection system which relies on only one predictor.